Self-Assembly of 3D DNA Crystals Containing a Torsionally Stressed Component. Issue 11 (16th November 2017) - Hernandez, Carina; Birktoft, Jens J.; Ohayon, Yoel P.; Chandrasekaran, Arun Richard; Abdallah, Hatem; Sha, Ruojie; Stojanoff, Vivian; Mao, Chengde; Seeman, Nadrian C.
Summary: There is an increasing appreciation for structural diversity of DNA that is of interest to both DNA nanotechnology and basic biology. Here, we have explored how DNA responds to torsional stress by building on a previously reported two-turn DNA tensegrity triangle and demonstrating that we could introduce an extra nucleotide pair (np) into the original sequence without affecting assembly and crystallization. The extra np imposes a significant torsional stress, which is accommodated by global changes throughout the B-DNA duplex and the DNA lattice. The work reveals a near-atomic structure of naked DNA under a torsional stress of approximately 14%, and thus provides an example of DNA distortions that occur without a requirement for either an external energy source or the free energy available from protein or drug binding. Graphical Abstract: Highlights: DNA torsionally stressed by ∼14% has been incorporated into a crystal The crystal structure has been determined by single anomalous dispersion No nucleotides are extruded from the double helix The stressed double helix remains within the B-form family of structures Abstract : DNA is stressed within the living cell, but it is difficult to observe its structural details. Here, Hernandez et al. incorporate stressed DNA within a self-assembled crystal lattice and determine its structure. The structure shows that no nucleotides are extruded, and the DNA remains as a B-form duplex.